Task design for online learning: the case of middle school mathematics and science teachers - Daher, Wajeeh; Shayeb, Shaheen; Jaber, Reema; Dawood, Iman; Abo Mokh, Amnah; Saqer, Khitam; Bsharat, Maysa; Rabbaa, Mohammad (Frontiers in Education, 2023)
Teachers’ task design in the context of online learning has been little researched by educational researchers. The current research studies, based on the didactical situation theory and specifically situation types, the design of tasks by teachers who teach science or mathematics in the context of distance education. The participants were fourteen teachers. They were interviewed regarding the situation types that they used to design online tasks. We used both deductive and inductive methods to analyse the transcribed interviews. The research findings showed that the teachers utilized different categories of the situation types. Moreover, the teachers utilized three types of reference: the institution, the individual, and the tool. An attempt was made by the participating mathematics and science teachers to integrate argumentation into their designed tasks. Furthermore, the situation of communication was designed by the participating teachers to enable interaction between and inside different agents of the online education (students, teachers, and parents), while utilizing different communicational channels (mobile social networks, Zoom’s rooms, Zoom’s sessions, students’ home, and Google Classroom). The teachers designed situations of action to take care of the various aspects of learning; namely the cognitive, the social, the affective, and the psychological aspects.